Four weeks of high-intensity training in moderate, but not mild hypoxia improves performance and running economy more than normoxic training in horses - Mukai, K.; Ohmura, H.; Takahashi, Y.; Kitaoka, Y.; Takahashi, T. (Physiological Reports, 2021)
We investigated whether horses trained in moderate and mild hypoxia demonstrate greater improvement in performance and aerobic capacity compared to horses trained in normoxia and whether the acquired training effects are maintained after 2 weeks of post-hypoxic training in normoxia. Seven untrained Thoroughbred horses completed 4 weeks (3 sessions/week) of three training protocols, consisting of 2-min cantering at 95% maximal oxygen consumption ( VO2max) under two hypoxic conditions (H16, FIO2 = 16%; H18, FIO2 = 18%) and in normoxia (N21, FIO2 = 21%), followed by 2 weeks of post-hypoxic training in normoxia, using a randomized crossover study design with a 3-month washout period. Incremental treadmill tests (IET) were conducted at week 0, 4, and 6. The effects of time and groups were analyzed using mixed models. Run time at IET increased in H16 and H18 compared to N21, while speed at VO? 2max was increased significantly only in H16. VO? 2max in all groups and cardiac output at exhaustion in H16 and H18 increased after 4 weeks of training, but were not significantly different between the three groups. In all groups, run time, VO? 2max, VVO2max, Q? max, and lactate threshold did not decrease after 2 weeks of post-hypoxic training in normoxia. These results suggest that 4 weeks of training in moderate (H16), but not mild (H18) hypoxia elicits greater improvements in performance and running economy than normoxic training and that these effects are maintained for 2 weeks of post-hypoxic training in normoxia.